Molecular T-cell‒mediated rejection in transbronchial and mucosal lung transplant biopsies is associated with future risk of graft loss - Halloran, Kieran; Parkes, Michael D; Timofte, Irina; Snell, Gregory; Westall, Glen; Havlin, Jan; Lischke, Robert; Hachem, Ramsey; Kreisel, Daniel; Levine, Deborah; Kubisa, Bartosz; Piotrowska, Maria; et al. (The Journal of heart and lung transplantation, 2020)
BACKGROUND: We previously developed molecular assessment systems for lung transplant transbronchial biopsies (TBBs) with high surfactant and bronchial mucosal biopsies, identifying T-cell‒mediated rejection (TCMR) on the basis of the expression of rejection-associated transcripts, but the relationship of rejection to graft loss is unknown. This study aimed to develop molecular assessments for TBBs and mucosal biopsies and to establish the impact of molecular TCMR on graft survival. METHODS: We used microarrays and machine learning to assign TCMR scores to an expanded cohort of 457 TBBs (367 high surfactant plus 90 low surfactant) and 314 mucosal biopsies. We tested the score agreement between TBB-TBB, mucosal-mucosal, and TBB-mucosal biopsy pairs in the same patient. We also assessed the association of molecular TCMR scores with graft loss (death or retransplantation) and compared it with the prognostic associations for histology and donor-specific antibodies. RESULTS: The molecular TCMR scores assigned in all the TBBs performed similarly to those in high-surfactant TBBs, indicating that variation in alveolation in TBBs does not prevent the detection of TCMR. Mucosal biopsy pieces showed less piece-to-piece variation than TBBs. TCMR scores in TBBs agreed with those in mucosal biopsies. In both TBBs and mucosal biopsies, molecular TCMR was associated with graft loss, whereas histologic rejection and donor-specific antibodies were not. CONCLUSIONS: Molecular TCMR can be detected in TBBs regardless of surfactant and in mucosal biopsies, which show less variability in the sampled tissue than TBBs. On the basis of these findings, molecular TCMR appears to be an important predictor of the risk of future graft failure. TRIAL REGISTRATION: ClinicalTrials.gov NCT02812290.
Keywords: Lung Transplantation; Lung; respirační sliznice; Graft Rejection; Graft Survival; Biopsy; prognóza; lidé; ženské pohlaví; Risk Factors; transplantace plic; rizikové faktory; T-Lymphocytes; buněčná imunita; přežívání štěpu; Female; mužské pohlaví; Respiratory Mucosa; Machine Learning; plíce; strojové učení; Humans; rejekce štěpu; bronchy; prospektivní studie; Male; Bronchi; biopsie; T-lymfocyty; Prognosis; Prospective Studies; Immunity, Cellular